2022
DOI: 10.1002/jctb.7211
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of coal gangue for preparing high‐silica porous materials with excellent ad/desorption performance on VOCs

Abstract: BACKGROUND: Coal gangue causes a series of environmental problems due to its low utilization rate and high amount of hoarding. However, the preparation of porous materials with coal gangue is an effective method of resource utilization. Mesoporous silica and meso-microporous ZSM-5 were prepared with alkali melting activation-acid leaching and hydrothermal synthesis, respectively. The orthogonal experiment was used to explore the optimal preparation conditions for mesoporous silica. Meso-microporous ZSM-5 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Han et al 87 introduced a water-soluble polyacrylamide (PAM) hydrogel into the SAPO-34 synthesis system and prepared hierarchical SAPO-34 with both micropores and mesopores, whose catalytic life is prolonged by about three times with highly enhanced adsorption performance. Jiang et al 88 reported meso–microporous ZSM-5 by hydrothermal synthesis, and excellent adsorption and desorption performance (the adsorption capacity is up to 47.02 mg g −1 ), water resistance (the adsorption capacity decreased only 4.64%), and renewability (the adsorption and desorption efficiency are up to 95% and 97%, respectively) were achieved.…”
Section: Classification and Modification Of Adsorbentsmentioning
confidence: 99%
“…Han et al 87 introduced a water-soluble polyacrylamide (PAM) hydrogel into the SAPO-34 synthesis system and prepared hierarchical SAPO-34 with both micropores and mesopores, whose catalytic life is prolonged by about three times with highly enhanced adsorption performance. Jiang et al 88 reported meso–microporous ZSM-5 by hydrothermal synthesis, and excellent adsorption and desorption performance (the adsorption capacity is up to 47.02 mg g −1 ), water resistance (the adsorption capacity decreased only 4.64%), and renewability (the adsorption and desorption efficiency are up to 95% and 97%, respectively) were achieved.…”
Section: Classification and Modification Of Adsorbentsmentioning
confidence: 99%
“…Combined methods, including the alkali fusion–hydrothermal method, ultrasonic–hydrothermal method, and ball milling−hydrothermal method, which have better performance than traditional methods, have also been tested 54,124 . As shown in Table 3, the synthetized zeolite types include NaA, 53,120,123,125 NaX, 52,118,124,126,127 NaY, 119 SSZ‐13, 128 ZSM‐5, 129 magnetic zeolite, 54 and zeolite/activated carbon composites 120,130 …”
Section: Porous Materials Made From Coal Ganguementioning
confidence: 99%
“…Coal gangue is a solid waste generated during coal mining [1], characterized by its low carbon content, which leads to a range of environmental issues due to its limited utilization and extensive accumulation [2][3][4]. Moreover, the presence of pyrite in coal gangue increases the risk of spontaneous combustion as sulfur easily oxidizes, further hindering comprehensive utilization [5,6].…”
Section: Introductionmentioning
confidence: 99%